北極の２地点でのフィルター捕集―光吸収法によるブラックカーボンの測定の評価 - 近藤, 豊 (2016)
これまでアラスカのバーローおよびスピッツベルゲンのニーオソルスンにおいて光吸収係数 (babs) の長期測定が、フィルター捕集―光吸収法に基づくPSAP測定器により行われてきた。しかし、ブラックカーボン（BC）と共存する他のエアロゾル成分のbabsへの影響については十分に評価されてこなかった。さらに、babsをBC質量濃度MBCに変換する（MBC = babs/MAC）際に必要な質量吸収断面積MACも異なった値が用いられてきた。我々はインレットを加熱し、揮発性のエアロゾルを除去するCOSMOS (continuous soot monitoring system)測定器を用いて2013-2015年にこれらの２地点でbabsの測定を3年間行ってきた。この測定に及ぼす不揮発性の海塩粒子の影響を室内実験と野外観測データから年平均で9%と推定した。さらにこれらの2地点でCOSMOS 測定値をElemental Carbon (EC)測定器とレーザー誘起白熱法による同時MBC測定値と比較し9%程度の一致を得た。またCOSMOSのMBCとPSAPによるbabs観測値には極めて高い相関があることを見出した。このCOSMOS-PSAP相関関係を用いて、これまでのPSAPによるbabs観測値をMBCに変換し、BCの季節変動や長期変化を求めた。また従来の異なった測定法とCOSMOS測定法とを比較し、従来の観測法の問題を評価した。これらの研究により、北極におけるBCの高精度測定を初めて確立することができた。さらに気候モデルにより計算される北極BC濃度を定量的に検証することが可能となった。 Long-term measurements of the light absorption coefficient (babs) obtained with a particle soot absorption photometer (PSAP), babs (PSAP), have been previously reported for Barrow, Alaska, and Ny-Ålesund, Spitsbergen, in the Arctic. However, the effects on babs of other aerosol chemical species co-existing with black carbon (BC) have not been critically evaluated. Furthermore, different mass absorption cross section (MAC) values have been used to convert babs to BC mass concentration (MBC = babs/MAC). We used a continuous soot monitoring system calledCOSMOS, which uses a heated inlet to remove volatile aerosol compounds, to measure babs [babs (COSMOS)] at these sites for about 3 years between 2012 and 2015. Field measurements and laboratory experiments have suggested that babs (COSMOS) is affected by about 9% on average by sea-salt aerosols. MBC values derived by COSMOS [MBC (COSMOS)] using MAC values obtained by our previous studies agreed to within 9% with elemental carbon concentrations at Barrow measured over 11 months, indicating that the accuracy of MBC (COSMOS) is good at that site. babs (PSAP) was systematically higher than babs(COSMOS), by 22% at Barrow (PM1) and by 43% at Ny-Ålesund (PM10). Using babs (COSMOS) as a reference, we derived MBC (PSAP) from babs (PSAP) measured since 1998. We also established the seasonal ...